V3-Loop genotypes do not predict maraviroc susceptibility of CCR5-tropic virus or clinical response through week 48 in HIV-1–infected, treatment-experienced persons receiving optimized background regimens. (July 2021) - Lewis, ME; Simpson, P; Mori, J; Jubb, B; Sullivan, J; McFadyen, L; van der Ryst, E; Craig, C; Robertson, DL; Westby, M
Viruses from 15 of 35 maraviroc-treated participants with virologic failure and CCR5-tropic (R5) virus in the MOTIVATE studies at Week 24 had reduced maraviroc susceptibility. On-treatment amino acid changes were observed in the viral envelope glycoprotein 120 third variable (V3)–loop stems and tips and differed between viruses. No amino acid change reliably predicted reduced susceptibility, indicating that resistance was genetic context–dependent. Through Week 24, poor adherence was associated with maraviroc-susceptible virologic failure, whereas reduced maraviroc susceptibility was associated with suboptimal background regimen activity, highlighting the importance of overall regimen activity and good adherence. Predictive values of pretreatment V3-loop sequences containing these Week 24 mutations or other variants present at >3% in pretreatment viruses of participants with virologic failure at Week 48 were retrospectively assessed. Week 48 clinical outcomes were evaluated for correlates with pretreatment V3-loop CCR5-tropic sequences from 704 participants (366 responders; 338 virologic failures [83 with R5 virus with maraviroc susceptibility assessment]). Seventy-five amino acid variants with >3% prevalence were identified among 23 V3-loop residues. Previously identified variants associated with resistance in individual isolates were represented, but none were associated reliably with virologic failure alone or in combination. Univariate analysis showed virologic-failure associations with variants 4L, 11R, and 19S ( P  < 0.05). However, 11R is a marker for CXCR4 tropism, whereas neither 4L nor 19S was reliably associated with reduced maraviroc susceptibility in R5 failure. These findings from a large study of V3-loop sequences confirm lack of correlation between V3-loop genotype and clinical outcome in participants treated with maraviroc. Clinical trial registration numbers (ClinicalTrials.gov): NCT00098306 and NCT00098722